Association Between Preoperative Oral Antibiotics and the Incidence of Postoperative Clostridium difficile Infection in Adults Undergoing Elective Colorectal Resection: A Systematic Review and Meta-analysis. Issue 4 (April 2020) - Khorasani, Sepehr; Dossa, Fahima; McKechnie, Tyler; Englesakis, Marina; Brar, Mantaj S.; de Buck van Overstraeten, Anthony
Abstract : BACKGROUND: The risk of postoperative Clostridium difficile infection in patients receiving preoperative oral antibiotics remains controversial and a potential barrier for implementation. OBJECTIVE: The purpose of this study was to determine the association between preoperative oral antibiotics and the incidence of postoperative C difficile infection in patients undergoing colorectal surgery. DATA SOURCES: Medline, PubMed (not Medline), Embase, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Web of Science were searched for articles published up to September 2018. STUDY SELECTION: Randomized controlled trials and observational studies that compared bowel preparation regimens in adult patients who underwent colorectal surgery were selected. MAIN OUTCOME MEASURE: The incidence of postoperative C difficile infection in adults receiving oral antibiotics versus no oral antibiotics was used as the primary outcome. ORs were pooled using generalized linear/mixed effects models. RESULTS: Fourteen randomized controlled trials and 13 cohort studies comparing bowel preparation with oral antibiotics to those without oral antibiotics were identified. The pooled OR from 4 eligible randomized controlled trials was suggestive of a greater odds of C difficile infection in the oral antibiotic group (OR = 4.46 (95% CI, 0.96–20.66)); however, the absolute incidence of C difficile infection was extremely low (total 11 events among 2753 patients). The pooled OR from 6 eligible cohort studies did not demonstrate a significant difference in the odds of C difficile infection (OR = 0.88 (95% CI, 0.51–1.52)); again, a very low absolute incidence of C difficile infection was identified (total 830 events among 59, 960 patients). LIMITATIONS: This meta-analysis was limited by the low incidence of C difficile infection reported in the studies and the low number of randomized controlled trials included. CONCLUSIONS: The incidence of C difficile infection in patients who undergo colorectal surgery is very low, regardless of bowel preparation regimen used. Considering the beneficial role of oral antibiotics in reducing surgical site infection, the fear for C difficile infection is not sufficient to omit oral antibiotics in this setting. SYSTEMATIC REVIEW REGISTRATION NUMBER: PROSPERO – IDCRD42018092148. Abstract : Supplemental Digital Content is available in the text.